Analysis of perceived price and product quality on repurchase intention with customer satisfaction as intervening variable (Shishaboss Surabaya) - Hamid Alhamid, Muhammad Syerif; Wirawan, Wirawan (Institute of Computer Science (IOCS), 2025)
This study aims to examine the influence of price perception factors, product quality, customer satisfaction on repurchase intention. The variables studied were perceived price, product quality, customer satisfaction, and repurchase intention. The research respondents were 190 Shisaboss consumers in Surabaya, who were taken by purposive sampling method. The analysis used is PLS. The results showed that perceived price and product quality each had a significant positive effect on customer satisfaction and repurchase intention, and customer satisfaction also had a significant positive effect on repurchase intention. based on research findings, alternative strategies that can be implemented Ensure that prices are considered reasonable and in accordance with product quality. Offer packages, discounts, or bundles that are in line with the price to attract price-sensitive customers